(Dis)order in the Court: Examining Neighborhood Disorder Prosecutions in Miami-Dade County. (10th November 2018) - Petersen, Nick; Omori, Marisa; Lautenschlager, Rachel
Abstract: This study examines race, space, perceptions of disorder, and nuisance crime prosecution in Miami-Dade County, Florida. Research has examined nuisance policing, yet little attention has been devoted to nuisance crime prosecutions, especially at the neighborhood level. Aggregating data on defendants arrested for nuisance offenses from 2012 to 2015 up to the neighborhood level, we estimate count models for pretrial detention, case acceptance, conviction, and sentencing outcomes in neighborhoods. We find two patterns of nuisance crime prosecution. Drug disorder prosecutions are concentrated in economically disadvantaged neighborhoods with large Black defendant populations, suggesting a more suppressive treatment of these "marginalized" spaces. In contrast, greater enforcement of homelessness and alcohol nuisance crimes in White non-Hispanic neighborhoods suggests disorder prosecutions are also used to impose order and containment in more economically "prime" spaces. These countervailing patterns highlight the spatial contingency of nuisance enforcement, whereby prosecutors differentially enforce nuisance crimes in prime and marginalized spaces.